Edukasi Perilaku Anti Bullying Pada Siswa SMP Muhammadiyah 1 Kota Ternate - Fiki Febrian Dwi Prasetya; Ika Suarsi; Dwi Fitriani (LPPM IAIN Sorong, 2025)
This community service program aims to provide education about anti-bullying behavior to junior high school students at SMP Muhammadiyah 1 Kota Ternate. Bullying in schools is a social issue that can have serious impacts on students' psychological well-being and academic achievement. The program was carried out through lectures, discussions, pre-test and post-test evaluations. The results showed an increase in students understanding of the negative impacts of bullying and how to prevent it. This program is expected to contribute to the creation of a safe and conducive school environment.